The impact of macroeconomic variables on exchange rate uncertain - Jane Kaboro; Naftaly Mose (Financial Internet Quarterly, 2021)
Macroeconomic convergence is critical for member states to achieve the level of harmonization required for establishing a stable and resilient monetary union. The East African Community (EAC) member states, therefore, established set targets for macroeconomic convergence, intending to eliminate exchange rate uncertainty within the bloc and reduce the costs of the monetary union. However, recent empirical studies indicate that the rate of convergence of the member states to the set macroeconomic targets has been very slow, resulting in high exchange rate uncertainty within the region. It is against this backdrop that this research was conceptualized to examine the influence of convergence in macroeconomic variables on the exchange rate uncertainty of EAC states using secondary panel data. The study made use of standard deviation and the Levin Lin Chu (LLC) test to determine convergence and unit root respectively. The panel ordinary least squares (OLS) regression findings showed that all the explanatory variables had a negatively significant effect on exchange rate uncertainty. This implies that convergence in macroeconomic variables among the member countries slows exchange rate uncertainty. Thus, policy should be made towards controlling this negative effect resulting from macroeconomic variables as East Africa bids for monetary union.
Keywords: E44; F15; F31; F45; 330; macroeconomic; exchange rate; regional integration; monetary union